ANALISIS ARAH DAN KECEPATAN ANGIN DENGAN APLIKASI WRPLOTS - Lusiani Lusiani; Teguh Wardoyo (Majalah Ilmiah Bahari Jogja, 2017)
The research was conducted at one point in Cilacap Waters in order toanalyze wind direction and speed with WRPLOTS application in 1 year periodfrom January to December 2015. Data obtained from BMKG Cilacap withdetails of wind direction and speed every hour (24 hours). Based on thepercentage of wind direction and speeds studied over the course of a year(January to December 2015) shows that winds move with wind speeds movingat top speeds of more than 22 knots with a 29.0% percentage rate and movingaround east and south.Key words: Wind, water, WRPLOTS